SOCIO-PSYCHOLOGICAL FEATURES OF FAMILY CRISES - Gaibova Nargiza Anorbaevna (Web of Journals Publishing, 2024)
This article analyzes family psychology and socio-psychological characteristics of crises in the family. The article presents research and summary information on this issue.
Keywords: family, psychology, psychology of family relations, crises, family psychotherapy, adaptation.